Exploring the Role of Paeonia emodi (Ood-e-Saleeb) in Neurological Health: Traditional Uses and Modern Pharmacological Insights: A Review - Hayat , Tooba; Latafat , Tabassum; Naseer , Mursaleen; Azmat, Jamal; Ali , S Javed; Sadaf , Sadaf (Journal of Drug Delivery and Therapeutics, 2025)
Ood-e-Saleeb, derived from Paeonia emodi Wall. (Ranunculaceae), is a medicinal herb extensively used in Unani medicine, particularly for neurological disorders. Found in the western temperate Himalayas, its roots, seeds, and flowers exhibit significant therapeutic properties. Traditionally, it has been utilized as a nervine tonic, nerve stimulant, and antispasmodic agent in conditions like paralysis (Fālij), facial palsy (Laqwa), tremors (Ri‘sha), epilepsy (Ṣar‘), and hysteria (Ikhtināq al-Raḥim). Recent pharmacological studies highlight its neuroprotective potential, particularly in diabetic peripheral neuropathy, where it modulates oxidative stress, inflammation, and neuronal apoptosis. Bioactive compounds such as paeoniflorin, flavonoids, and tannins contribute to its effects by enhancing neurogenesis, regulating neurotransmitter activity, and protecting against neuronal degeneration. Its ability to improve nerve function in diabetic neuropathy is linked to mechanisms involving advanced glycation end products (AGEs) and NF-κB pathway modulation. This review consolidates its traditional and modern pharmacological relevance, emphasizing its role in neurological disorders, including diabetic peripheral neuropathy, and its potential for further research and therapeutic applications. Keywords: Ood-e-Saleeb, Neurological Disorders, Diabetic Peripheral Neuropathy, Paeonia emodi, Neuroprotection